Building students' entrepreneurial mindsets: Results from an intervention at a Russian university. Issue 2 (July 2020) - Hultén, Peter; Tumunbayarova, Zhargal
Highlights: We used a quasi-experimental research design to examine the effects of an intervention to enhance students' entrepreneurial mindset. The applied intervention method has a positive impact on the treatment group's entrepreneurial mindset. The intervention is effective in creating a learning climate, which support the initial build-up of students' entrepreneurial mindset. The effect of the intervention is likely to be short-lived due to the lack of structures to support entrepreneurial behavior.